Svalbard reindeer and its interaction with extreme polar environment - Kavanová, Veronika (Jihočeská univerzita, 2022)
Two distinct populations of Svalbard reindeer are compared based on their antler parameters. Relative antler size and number of tines are supposed to reflect well environmental conditions of the sedentary population within the growing season. Both studied populations are well spatially isolated due to high mountain ridges, glaciers and fjords. The population in Petuniabukta occupies sparsely vegetated region with harsh climatic conditions, whereas Skansbukta represents area with continuous tundra vegetation, milder climatic conditions and consequently also longer vegetation season. These environmental factors probably lead to significant differences in relative antler size and number of tines. Skansbukta population has larger relative antler size and higher number of tines than the population in Petuniabukta.
Svalbard reindeer and its interaction with extreme polar environment
Keywords: Svalbard reindeer; antlers; population characteristics; environmental conditions; Svalbard reindeer; antlers; population characteristics; environmental conditions